PENERAPAN DATA MINING DALAM MENENTUKAN PEMBINAAN KOPERASI (STUDI KASUS : DINAS KOPERASI DAN UKM KABUPATEN KOTAWARINGIN TIMUR) - Yuni Ambar S; Kusrini Kusrini; Henderi Henderi (Universitas Janabadra, 2019)
Currently coaching for cooperatives in the East Kotawaringin Regency Government is very necessary because of the existence of newly established cooperatives and those that have long been standing down and slow in the implementation of Annual Member Meetings (RAT). With the number of cooperatives currently the Cooperative Office lacks supervisory human resources, therefore cooperatives need to be taken into account that are prioritized on coaching. One way to dig data is Data Mining using statistical methods using the K-NN algorithm. In this study, the K-NN Algorithm is used in determining the Cooperative that is feasible for the coach. The results obtained from this study were to obtain the results of the classification of cooperatives that deserved coaching with an accuracy of 96.33 percent. Keywords : Coaching, Clasification, K-Nearest Neighbour